UV-cured hyperbranched polyester polythiol(H20-SH)-epoxy acrylate networks: Preparation, thermal and mechanical properties. Issue 10 (3rd October 2017) - Guan, Xiao-Xiao; Gan, Jian-Qun; Chen, Guo-Kang; Huang, Xiao-Mei; Lu, Man-Geng; Wu, Kun; Liang, Li-Yan; Shi, Jun
ABSTRACT: A hyperbranched polyester polythiol(H20-SH) was synthesized and characterized by FTIR spectral analysis, 1 H-NMR spectral analysis and GPC analysis. H20-SH was added into the formulation of UV-curable epoxy acrylate networks based on thiol-acrylate chemistry. The effects of H20-SH on polymerization kinetics, thermal and mechanical properties of thiol-epoxy acrylate networks were investigated by Real-time infrared spectroscopy, dynamic mechanical analysis (DMA), thermogravimetric (TGA), tensile test and water absorption characterization. Results show that epoxy acrylate resin with the addition of H20-SH massively reduces oxygen inhibition, improves the uniformity of cured films and enhances the tensile strength of the films. However, the thermal stability and glass transition temperature (Tg ) decreases with the increasing amount of H20-SH.